Towards using the instrumented Timed Up-and-Go test for screening of sensory system performance for balance control in older adults - Gerhardy, Thomas; Gordt-Oesterwind, Katharina; Jansen, Carl-Philipp; Schwenk, Michael (Sensors, 2019)
Background: Decreasing performance of the sensory systems' for balance control, including the visual, somatosensory and vestibular system, is associated with increased fall risk in older adults. A smartphone-based version of the Timed Up-and-Go (mTUG) may allow screening sensory balance impairments through mTUG subphases. The association between mTUG subphases and sensory system performance is examined. Methods: Functional mobility of forty-one community-dwelling older adults (>55 years) was measured using a validated mTUG. Duration of mTUG and its subphases 'sit-to-walk', 'walking', 'turning', 'turn-to-sit' and 'sit-down' were extracted. Sensory systems' performance was quantified by validated posturography during standing (30 s) under different conditions. Visual, somatosensory and vestibular control ratios (CR) were calculated from posturography and correlated with mTUG subphases. Results: Vestibular CR correlated with mTUG total time (r = 0.54; p = 0.01), subphases 'walking' (r = 0.56; p = 0.01), and 'turning' (r = 0.43; p = 0.01). Somatosensory CR correlated with mTUG total time (r = 0.52; p = 0.01), subphases 'walking' (r = 0.52; p = 0.01) and 'turning' (r = 0.44; p = 0.01). Conclusions: Supporting the proposed approach, results indicate an association between specific mTUG subphases and sensory system performance. mTUG subphases 'walking' and 'turning' may allow screening for sensory system deterioration. This is a first step towards an objective, detailed and expeditious balance control assessment, however needing validation in a larger study.
Gesehen am 07.02.2019